Review of Evaluation and Valuation Methods for Cetacean Regulation and Maintenance Ecosystem Services With the Joint Cetacean Protocol Data - Sheehy, Jack Michael; Taylor, Nicola L; Zwerschke, Nadescha; Collar, Mark; Morgan, Vicky; Merayo, Eugenia (Frontiers in Marine Science, 2022)
Cetaceans provide a range of ecosystem services of value to anthropogenic interests. Following the Common International Classification of Ecosystem Services (CICES) these are categorised as regulation and maintenance, provisioning, and cultural values. This study focuses on those of importance to climate change mitigation through regulation and maintenance. Under regulation and maintenance, cetaceans can store, transport, and influence stocks of carbon through: climate regulation through carbon sequestration, enhanced biodiversity and ecosystem potential, and enhanced primary productivity. ‘Climate regulation through carbon sequestration’ can be quantified as carbon fixation through living biomass and ‘whale-falls’. Cetacean populations store significant stocks of carbon in living biomass. After death, sinking whale carcasses, ‘whale-falls’, provide a significant transfer of biomass and nutrients to benthic sediments and support deep sea ecosystems. During their lifespan, cetaceans also disperse nutrients through feeding and excretion both horizontally through the ‘whale-conveyor’ and vertically through the ‘whale pump’. As nutrient limitations hinder phytoplankton growth, these processes can be quantified as the increased potential of phytoplankton carbon fixation from cetacean driven nutrient cycling. Enhanced biodiversity, ecosystem potential, and primary productivity can be quantified as carbon fixation through nutrient cycling. This study reviews the evaluative and valuative techniques used in cetacean ecosystem service research and adapts and applies them to the Joint Cetacean Protocol (JCP) data which details cetacean abundance and distribution in Europe. They are then reviewed with regards to their robustness, application in markets, and in decision making processes. Cetacean populations are estimated to contain 2 Mt C, cycle 60,000 t N yr-1, and impact carbon fluxes by as much as 22 Mt C yr-1 in the survey area. The values highlight key areas for cetacean conservation: the Outer Hebrides, west of south Wales, around the Isle of Man, to the east of England, and to the north-east of the Shetland Islands. There is, however, large uncertainty in the evaluative processes used; nutrient cycling models presented in this study don’t capture removal of excess nutrients, or the values of enhanced biodiversity and ecosystem potential. As such, they are not sufficiently robust to quantify market values but highlight key areas for future research on climate change mitigation through conservation. Key areas of future research include phytoplankton uptake rates of nitrogen and phosphorus in nutrient limited waters, quantification of ‘enhanced biodiversity and ecosystem potential’, and nutrient removal from coastal waters.